Metagenomic Insights into the Uncultured Diversity and Physiology of Microbes in Four Hypersaline Soda Lake Brines - Vavourakis, Charlotte D.; Ghai, Rohit; Rodriguez-Valera, Francisco; Sorokin, Dimitry Y.; Tringe, Susannah G.; Hugenholtz, Philip; Muyzer, Gerard (Frontiers in Microbiology, 2016)
Soda lakes are salt lakes with a naturally alkaline pH due to evaporative concentration of sodium carbonates in the absence of major divalent cations. Hypersaline soda brines harbor microbial communities with a high species- and strain-level archaeal diversity and a large proportion of still uncultured poly-extremophiles compared to neutral brines of similar salinities. We present the first ‘metagenomic snapshots’ of microbial communities thriving in the brines of four shallow soda lakes from the Kulunda Steppe (Altai, Russia) covering a salinity range from 170 to 400 g/L. Both amplicon sequencing of 16S rRNA fragments and direct metagenomic sequencing showed that the top-level taxa abundance was linked to the ambient salinity: Bacteroidetes, Alpha- and Gammaproteobacteria were dominant below a salinity of 250 g/L, Euryarchaeota at higher salinities. Within these taxa, amplicon sequences related to Halorubrum, Natrinema, Gracilimonas, purple non-sulfur bacteria (Rhizobiales, Rhodobacter and Rhodobaca) and chemolithotrophic sulfur oxidizers (Thioalkalivibrio) were highly abundant. Twenty-four draft population genomes from novel members and ecotypes within the Nanohaloarchaea, Halobacteria and Bacteroidetes were reconstructed to explore their metabolic features, environmental abundance and strategies for osmotic adaptation. The Halobacteria- and Bacteroidetes-related draft genomes belong to putative aerobic heterotrophs, likely with the capacity to ferment sugars in the absence of oxygen. Members from both taxonomic groups are likely involved in primary organic carbon degradation, since some of the reconstructed genomes encode the ability to hydrolyze recalcitrant substrates, such as cellulose and chitin. Putative sodium-pumping rhodopsins were found in both a Flavobacteriaceae- and a Chitinophagaceae-related draft genome. The predicted proteomes of both the latter and a Rhodothermaceae-related draft genome were indicative of a ‘salt-in’ strategy of osmotic adaptation. The primary catabolic and respiratory pathways shared among all available reference genomes of Nanohaloarchaea and our novel genome reconstructions remain incomplete, but point to a primarily fermentative lifestyle. Encoded xenorhodopsins found in most drafts suggest that light plays an important role in the ecology of Nanohaloarchaea. Putative encoded halolysins and laccase-like oxidases might indicate the potential for extracellular degradation of proteins and peptides, and phenolic or aromatic compounds.